2019
DOI: 10.3892/etm.2019.8007
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA‑3934‑5p induces apoptosis and inhibits the proliferation of neuroblastoma cells by targeting TP53INP1

Abstract: Neuroblastoma is the most common pediatric extracranial solid tumour in the world. miRNAs are a group of endogenous small non-coding RNAs that act on target genes to serve critical roles in many biological processes. Presently, the expression and role of miR-3934-5p in neuroblastoma remains unclear. Therefore, the aim of the present study was to investigate the expression of miR-3934-5p in neuroblastoma tissues and cell lines and to assess the role of miR-3934-5p in neuroblastoma. In the current study, the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
4
10
0
Order By: Relevance
“…Therefore, we focused on TP53INP1 for further exploration. This study showed that the TP53INP1 expression in OSCC is consistent with former research that it is often lost during cancer development from different organs [42][43][44] . It has been documented that TP53INP1 exerts tumor suppressor function through involvement in cell death, cell-cycle arrest and cellular migration [43][44][45].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, we focused on TP53INP1 for further exploration. This study showed that the TP53INP1 expression in OSCC is consistent with former research that it is often lost during cancer development from different organs [42][43][44] . It has been documented that TP53INP1 exerts tumor suppressor function through involvement in cell death, cell-cycle arrest and cellular migration [43][44][45].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it has been reported that miRNAs regulate cell viability by regulating TP53INP1 in other diseases. For example, Ye et al ( 38 ) reported that miR-3934-5p may inhibit the cell viability of neuroblastoma by targeting TP53INP1. TP53INP1 expression was negatively regulated by miR-301a, and TP53INP1/miR-301a was involved in gastric cancer cell viability ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…At rst, M, H, et al [25]demonstrated that EGFR agonist EREG has played an important role in tamoxifen-resistant breast cancer cells by activating EGFR signaling and its downstream glycolytic genes. It was further proved that EREG was a direct target of miR-186-3p, and tamoxifen downregulation of miR-186-3p could lead to upregulation of EREG in tamoxifen-resistant breast cancer cells [26]. Research by W, Y et al [26] found that miR-3934-5p…”
Section: Discussionmentioning
confidence: 99%
“…It was further proved that EREG was a direct target of miR-186-3p, and tamoxifen downregulation of miR-186-3p could lead to upregulation of EREG in tamoxifen-resistant breast cancer cells [26]. Research by W, Y et al [26] found that miR-3934-5p…”
Section: Discussionmentioning
confidence: 99%